Internet Routing With Lightweight Route Attestation (International Journal of Engineering and Computer Science, 2017)
The Internet routing system plays an essential role of gluing together tens of thousands of individual networks to create a global data delivery substrate. Over the years many efforts have been devoted to securing the routing system, the weak trust model in Border Gateway Protocol (BGP) introduces severe vulnerabilities for Internet routing including active malicious attacks and unintended misconfigurations. Although various secure BGP solutions have been proposed, the complexity of security enforcement and dataplane attacks still remain open problems. We propose TBGP, a trusted BGP scheme aiming to achieve high authenticity of Internet routing with a simple and lightweight attestation mechanism. TBGP introduces a set of route update and withdrawal rules that, if correctly enforced by each router, can guarantee the authenticity and integrity of route information that is announced to other routers in the Internet. To verify this enforcement, an attestation service running on each router provides interfaces for a neighbouring router to challenge the integrity of its routing stack, enforced rules, and the attestation service itself. If this attestation succeeds, the neighbouring router updates its routing table or announces the route to its neighbours, following the same rules. Thus, a router on a routing path only needs to verify one neighbour’s routing status to ensure that the route information is valid. Through this, TBGP builds a transitive trust relationship among all routers on a routing path. We implement a prototype of TBGP to investigate its practicality.